Peranan Pajak Progresif Kendaraan Bermotor dalam Tranportasi Kota Besar - Hanggoro Pamungkas (Bina Nusantara University, 2011)
Transportation in big cities has phenomenal progressrecenly, with growths in automotive vehicles number over the infrastructure and roads length. Jakarta as the bigest cityand the capital of Indonesia has stronger economics, wider areas, more automotive vehicles number, and its populations. Data in the survey, literatures, and analysis over three years in Jakarta, has shown fantastic changes of automotive vehicles number growth composition. Two wheels automotive vehicles growth and number are in the top rank from other categories. Survey of Jakarta has shown economics growth that has increased prosperity of some population group, caused to automotive ownership taxes increase. In the contrary it has also negative effects in inefficiency and national social cost caused from traffic problem. It is suggested that options possibility to overcome from traffic or transportation problem in Jakarta, especially related to traffic management or automotive vehicle ownership management.